2021
DOI: 10.1111/jdv.17441
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre open‐label study of apremilast in palmoplantar pustulosis (APLANTUS)

Abstract: Background Palmoplantar pustulosis (PPP) is a chronic skin disease with painful erythematous scaly or crusty lesions and pustules on the palms and soles. Apremilast is a phosphodiesterase 4 inhibitor that has proven effective in the therapy of psoriasis, psoriatic arthritis and in oral ulcers associated with Behcet’s disease. Objective To explore the efficacy of apremilast in PPP. Methods APLANTUS was a phase 2 single‐arm multicentre study of apremilast in 21 subjects with moderate‐to‐severe PPP. Primary endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Table 3 contains information about the main recent clinical trials regarding treatment of PP [ 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 ]. Ongoing clinical trials and other completed studies not included in Table 3 are reported in Table 4 .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 contains information about the main recent clinical trials regarding treatment of PP [ 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 ]. Ongoing clinical trials and other completed studies not included in Table 3 are reported in Table 4 .…”
Section: Treatmentmentioning
confidence: 99%
“…Nevertheless, high-quality evidence is lacking for most PPP treatments [ 171 ]. Other oral treatments include tetracyclines [ 171 ] and the phosphodiesterase inhibitor apremilast that has been described as effective in few patients with moderate-to-severe or refractory disease [ 10 , 146 , 172 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Topical corticosteroids, oral retinoids (i.e., acitretin), cyclosporine, methotrexate, TNF-α inhibitors (i.e., adalimumab), anti-IL-17 monoclonal antibody (i.e., secukinumab), anti-IL-23 monoclonal antibody (i.e., guselkumab), anti-IL-1β monoclonal antibodies (i.e., gevokizumab and canakinumab), IL-1R inhibitor (i.e., anakinra), PDE-4 inhibitor (i.e., apremilast) [3,4,7,9,[11][12][13][14].…”
Section: Generalized Pustular Psoriasis (Gpp)mentioning
confidence: 99%
“…There are limited case reports that demonstrate the therapeutic potential of apremilast for patients with PPPP and GPP [46][47][48]. APLANTUS was a 20-week, phase II open-label study that investigated the efficacy and safety of apremilast in patients with PPPP [14]. Patients who were enrolled saw a significant decrease in PPPASI, with 61.9% of patients achieving PPPASI-50 [14].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation